Rancang Bangun Aplikasi Informasi Promo UMKM di Daerah Kecamatan Penajam Berbasis Android - Sugianto, Febri (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
The UMKM Promo Information Application is an Android application that displays product promo information, news and the location of UMKMs in the Penajam District. This application provides information on UMKMs in Penajam and makes it easy for users to get information about existing promos by using electronic devices in the form of android-based gadgets. The purpose of this final project is to design and build an application system that can provide solutions as a medium of information in finding and getting promos for UMKM products in the Penajam area. The research method used is data collection, system design, code generation, testing and application implementation. The conclusion from the results of this final project is an android-based application that is designed to provide convenience in finding promo information for UMKMs in the Penajam District.